2022
DOI: 10.3233/cbm-210149
|View full text |Cite
|
Sign up to set email alerts
|

E2F1 transcriptionally regulates CCNA2 expression to promote triple negative breast cancer tumorigenicity

Abstract: BACKGROUND: Triple-negative breast cancer (TNBC) is a highly malignant breast cancer subtype with a poor prognosis. The cell cycle regulator cyclin A2 (CCNA2) plays a role in tumor development. Herein, we explored the role of CCNA2 in TNBC. METHODS: We analyzed CCNA2 expression in 15 pairs of TNBC and adjacent tissues and assessed the relationship between CCNA2 expression using the tissue microarray cohort. Furthermore, we used two TNBC cohort datasets to analyze the correlation between CCNA2 and E2F transcrip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…In addition, E2F1 regulates the expression of various cytokines and growth factor receptors to establish a feedback mechanism ( Ertosun et al, 2016 ). A recent research from Lu et al revealed that E2F1 transcriptionally regulated cell cycle regulator cyclin A2 (CCNA2) expression to promote tumorigenicity of TNBC ( Lu et al, 2021 ). Here, further study based on a dual-luciferase assay and a ChIP-qPCR assay revealed that RFWD3 could facilitate the binding of E2F1 to the BIRC5 promoter and transcriptionally activate BIRC5 by interacting with E2F1 in HCT-116 cells.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, E2F1 regulates the expression of various cytokines and growth factor receptors to establish a feedback mechanism ( Ertosun et al, 2016 ). A recent research from Lu et al revealed that E2F1 transcriptionally regulated cell cycle regulator cyclin A2 (CCNA2) expression to promote tumorigenicity of TNBC ( Lu et al, 2021 ). Here, further study based on a dual-luciferase assay and a ChIP-qPCR assay revealed that RFWD3 could facilitate the binding of E2F1 to the BIRC5 promoter and transcriptionally activate BIRC5 by interacting with E2F1 in HCT-116 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Cyclin A2 dominates the longest period of time in the late G1 phase and could bind to CDK2. Previous study has demonstrated that overexpression of cyclin A2 promotes TNBC proliferation, invasion, and migration while inhibiting apoptosis [44]. Cyclin D1 has been proven as an oncogenic factor since upregulation of cyclin D1 was related to poor cancer prognosis [45].…”
Section: Discussionmentioning
confidence: 99%
“…Hub proteins could be used for the development of therapeutic intervention. Cyclin A2 (CCNA2) regulates the cell cycle and contributes to tumor growth ( 47 ). Cyclin B1 (CCNB1) is a crucial mitosis initiator and controller ( 48 ).…”
Section: Discussionmentioning
confidence: 99%